Development of Learning Modules Based on Augmented Reality (AR) as a Means of Visualizing Abstract Concepts IPAS Theme Knowing Our Earth - Syahrir, Fitriani; Zulnuraini, Zulnuraini; Kamisani, Nurul; Azizah, Azizah; Pendit, Sinta Satria Dewi (Journal of Educational Sciences, 2025)
This study aims to develop an Augmented Reality (AR) based learning module as a means of visualizing abstract concepts in the subject of Natural and Social Sciences (IPAS) with the theme “Knowing Our Earth” for grade V elementary school students. The background of this research is based on the difficulty of students in understanding the abstract concepts of IPAS and the limitations of learning media used by teachers. This research uses the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation), with implementation up to the formative evaluation stage. The products developed are printed and digital modules equipped with 3D markers using the Assemblr Edu application, so that they can be visualized through smartphones. The results of validation by material experts obtained a score of 95%, media experts 99%, and users (teachers) of 96%, all of which were in the “very valid” category. The limited trial of 25 students showed a very positive response with a readability percentage of 85%. This module is considered to be able to increase students' interest and understanding of the material “Knowing Our Earth” with interactive and interesting concept visualization. Thus, this Augmented Reality-based learning module is worth using as an innovative learning media in improving the quality of IPAS learning in elementary schools.